Modernizing Trade in Pakistan : Policy Reform Handbook - World Bank Group (World Bank, Washington, DC, 2020)
This handbook intends to be a resource for those interested in trade policy reform, in Pakistan and elsewhere. It arose from the Pakistan trade and investment policy program (PTIPP). The PTIPP was designed to work on trade, competitiveness, and gender in Pakistan. This handbook focuses on two pillars of the PTIPP: trade policy and trade facilitation. The objective of the trade policy pillar was to develop a comprehensive medium-term regional trade strategy underpinned by high-quality analysis, in line with international good practice. The objective of the trade facilitation pillar was to reduce the time, cost, and documentation required to process exports and imports through key border posts, leading to a substantial increase in the volume of goods traded. To achieve these objectives, the PTIPP engaged with policy-making institutions, the private sector, including female entrepreneurs, and government to promote international trade, investment, gender equality, and regional integration. The authors focused on producing a document that not only lists results and recommendations but also guides the reader through how the analysis was conducted and how the recommendations were reached. This handbook also provides a set of guidelines for analyzing competitiveness in any country and shows how the lessons learned in Pakistan can apply to other economies. It will therefore be useful for teams conducting competitiveness analyses in other countries and regions.